Model Development of Children’s Language Skills Based on Digital Literacy - Probowati, Yeni; Kuswahono, Deny; Irmayanti, Nur (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
This research generally aims to develop a model of children’s language skills based on digital literacy in Pondok Benowo Indah RT 03 RW 08 Babat Jerawat, Pakal Surabaya. First, to determine the process or stages of learning language skills using narrative stories or fairy tales from a YouTube application that is watched by them and is accompanied by their parents. The two processes or stages of developing language skills are by retelling stories or fairy tales that they see with their parents and writing moral messages in the stories or fairy tales. The method used in this study is quantitative-qualitative (mix method). The data were analyzed using content analysis techniques. The data will be analyzed through the following steps: 1) classifying the data, 2) displaying the data, 3) interpreting the data, and 4) drawing a conclusion. The study intends to create and develop a role of language skills for the children who mostly like their devices compared to playing together with their peers outside the home. For parents, this model of language skills can later be applied at home when they are together and interact with their children. For children, this is a diversion from the gadgets they often hold when they are at home.